The colonial genealogies of political decay and legitimation crises: An enquiry into the predicament of state-construction in post-colonial South Asia - Sanjeev, Kumar H.M. (India Quarterly)
This article is an attempt to conceptualise and theoretically explain the colonial genealogies of the processes of state-making and state-construction in post-colonial South Asia. In pursuit of this, the article seeks to theorise the colonial ways of providing a sense of fixity of political territoriality, held together by colonially crafted institutions of metropolitan governance, as an independent variable in determining the nature of the processes of state-making and state-construction in the region. On this count, an enquiry into the complex trajectory of these post-colonial political processes, which are the dependent variables for this article, is the fundamental problematic of analysis. This problematic would be decoded with the help of a dual conceptual framework, involving what Samuel Huntington designates as political decay and the legitimation crisis given by Jurgen Habermas. In the context of South Asia, the predicaments of political decay and legitimation crisis, according to this article, manifest as after-effects of engagement on the part of the region$1 (Bs post-colonial polities with the imported values of colonial modernity and neoliberal economic reforms. By drawing instances from two countries of the Indian subcontinent, Pakistan and Bangladesh, the article tries to show how these after-effects have played out in the form of a tumultuous political history of the processes of state-making and state-construction. The article, in this way, is an attempt to theorise the inter-sectionalities between the colonial and post-colonial periods of South Asia. This has been done here by problematising such a historical inter-sectionality from the perspective of the two intervening variables$1 (Bthe received values of colonial metropolis and the morals of modernity$1 (Bmediated through neoliberal economic reforms. Reproduceds
Keywords: Political decay, Huntington, Legitimation crisis, Habermas, Post-colonial states